2018
DOI: 10.1080/00365521.2018.1447596
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cytomegalovirus by immunohistochemistry of colonic biopsies and quantitative blood polymerase chain reaction: evaluation of agreement in ulcerative colitis

Abstract: In active CMV colitis, the specificity and negative predictive value of blood PCR are high, while the sensitivity grows with the intensity of colon infection. A highly positive result could justify the administration of antiviral treatment being brought forward in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[8] CMV colitis is most commonly associated with UC, followed by Crohn disease (CD), immunosuppression, and hematological malignancy. [9–11] In the present study, some of the patients had comorbidities that caused additional immunosuppression in addition to IBD, such as acquired immunodeficiency syndrome, a history of liver transplantation, and breast cancer. Previous studies have reported that the prevalences of CMV colitis and CMV disease are significantly higher in UC than in CD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[8] CMV colitis is most commonly associated with UC, followed by Crohn disease (CD), immunosuppression, and hematological malignancy. [9–11] In the present study, some of the patients had comorbidities that caused additional immunosuppression in addition to IBD, such as acquired immunodeficiency syndrome, a history of liver transplantation, and breast cancer. Previous studies have reported that the prevalences of CMV colitis and CMV disease are significantly higher in UC than in CD.…”
Section: Discussionmentioning
confidence: 93%
“…Quantitative CMV-DNA PCR in tissue and blood is the most commonly used technique for the diagnosis of CMV infection. [9] CMV-DNA PCR testing in the blood can diagnose CMV viremia and potentially detect CMV throughout the body; however, it does not indicate definitive CMV infection in the colonic mucosa. Therefore, CMV-DNA positivity should be investigated using PCR in colonic mucosa samples for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective study reported that five or more CMV-IHC-positive cells per biopsy section were indicative of a greater colectomy risk [23]. Another retrospective comparative study of CMV-IHC and bCMV-PCR from the same authors reported an association between the highest viremia quartile and a positive CMV-IHC-result which may justify the administration of an antiviral treatment in selected patients [24]. In our cohort, however, we were not able to show that quantitative bCMV-PCR results permitted a better prediction of the subsequent course of UC than the qualitative ones alone.…”
Section: In Inflamed Mucosa Indicates a Severe Clinical Coursementioning
confidence: 99%
“…Current methods used to diagnose CMV disease include DNA hybridization and PCR. Detecting CMV using molecular methods such as quantitative PCR (qPCR) is fast, highly sensitive, and more objective than IHC [16][17][18][19]. It is surprising, therefore, that the role of qPCR for diagnosis of CMV disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%